2022
DOI: 10.3390/microorganisms10050941
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Clonal Lineages of Staphylococcus aureus from Cattle, Their Handlers, and Their Surroundings: A Cross-Sectional Study from the One Health Perspective

Abstract: Staphylococcus aureus have been progressively identified in farm animals and in humans with direct contact with these animals showing that S. aureus may be a major zoonotic pathogen. Therefore, we aimed to isolate S. aureus from cows, their handlers, and their immediate surroundings, and to investigate the antimicrobial resistance and genetic lineages of the isolates. Mouth and nose swabs of 244 healthy cows (195 Maronesa, 11 Holstein-Friesians, and 28 crossbreeds), 82 farm workers, 53 water and 63 soil sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
3
7
0
Order By: Relevance
“…In three of our previous studies, the frequency of S. aureus and MRSA was investigated in healthy humans without recent contact with the hospital environment but with direct contact with livestock and pets, namely, cows, donkeys and dogs. Humans handling cows and donkeys were not colonized by MRSA but were S. aureus carriers [ 70 , 71 ]. However, several different clonal lineages were detected among humans, including ST398 and ST97 (animal-associated) and ST30 and ST8 (community-associated).…”
Section: Mrsa In Portugalmentioning
confidence: 99%
See 1 more Smart Citation
“…In three of our previous studies, the frequency of S. aureus and MRSA was investigated in healthy humans without recent contact with the hospital environment but with direct contact with livestock and pets, namely, cows, donkeys and dogs. Humans handling cows and donkeys were not colonized by MRSA but were S. aureus carriers [ 70 , 71 ]. However, several different clonal lineages were detected among humans, including ST398 and ST97 (animal-associated) and ST30 and ST8 (community-associated).…”
Section: Mrsa In Portugalmentioning
confidence: 99%
“…Nevertheless, other Portuguese studies have reported that 13.1% of the cows screened were colonized by S. aureus. The most common S. aureus lineage found was ST6-t16615 and most isolates were susceptible to all antimicrobials tested or showed resistance to penicillin [ 71 ]. In a study carried out by our research team, 30% of the healthy quails screened carried MRSA and only STs (ST398 and ST6831) and spa -types (t011 and t9747) were detected [ 37 ].…”
Section: Mrsa In Portugalmentioning
confidence: 99%
“…The usage of antibiotics creates selective pressure, driving antimicrobial resistance (AMR) in both human and veterinary medicine [ 14 , 15 ]. The spread of AMR S. aureus strains between livestock and humans underscores the need for a One Health approach, with several studies indicating the zoonotic potential of certain S. aureus lineages [ 4 , 16 , 17 ]. Since cattle domestication, the proximity of humans and cows or the consumption of raw milk and dairy products have increased the risk of S. aureus spillovers [ 16 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance of pathogens is a significant and increasing problem in veterinary medicine [ 5 , 6 , 7 ]. Comprehensive efforts to control antibiotic resistance of bacterial isolates from animals have been made, given the importance of the problem for animal health itself, as well as the animal–human interactions in a One Health approach [ 8 ].…”
Section: Introductionmentioning
confidence: 99%